2012
DOI: 10.1111/j.1600-051x.2012.01924.x
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative periodontal therapy of infrabony defects using minimally invasive surgery and a collagen‐enriched bovine‐derived xenograft: a 1‐year prospective study on clinical and aesthetic outcome

Abstract: RPT using minimally invasive surgery and a collagen-enriched bovine-derived xenograft demonstrated favourable clinical outcome after 1 year, even though soft tissue aesthetics could not be fully preserved. Defects with a non-supporting anatomy may be at risk for failure and advanced midfacial recession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 33 publications
0
46
0
2
Order By: Relevance
“…The minimally invasive surgical technique (MIST) was used in eleven studies by different authors (Aimetti et al, ; Cortelini et al, ; Cortellini et al, ; Cortellini & Tonetti, , ; Cortellini & Tonetti, , ; Cosyn et al, ; De Bruyckere et al, ; Ghezzi et al, ; Ribeiro, Casarin, Palma, et al, 2011a; Ribeiro, Casarin, Palma, et al, 2011b; Ribeiro et al, , ), with the aid of an operating microscope. It consists of an envelope full‐thickness flap extended to the buccal and lingual aspects of the two teeth adjacent to the defect to expose 1–2 mm of the residual bone crest; flaps are then repositioned without any coronal displacement, and the suturing approach consists of a single modified internal mattress suture.…”
Section: Resultsmentioning
confidence: 99%
“…The minimally invasive surgical technique (MIST) was used in eleven studies by different authors (Aimetti et al, ; Cortelini et al, ; Cortellini et al, ; Cortellini & Tonetti, , ; Cortellini & Tonetti, , ; Cosyn et al, ; De Bruyckere et al, ; Ghezzi et al, ; Ribeiro, Casarin, Palma, et al, 2011a; Ribeiro, Casarin, Palma, et al, 2011b; Ribeiro et al, , ), with the aid of an operating microscope. It consists of an envelope full‐thickness flap extended to the buccal and lingual aspects of the two teeth adjacent to the defect to expose 1–2 mm of the residual bone crest; flaps are then repositioned without any coronal displacement, and the suturing approach consists of a single modified internal mattress suture.…”
Section: Resultsmentioning
confidence: 99%
“…This ranged between 2 weeks [28] and 6 months [11,29,30]. No studies reported clinical and radiographic measures of intrabony defects before and after NSPT and often (55 % of papers) it was not clear exactly when after NSPT (if carried out) the baseline study measurements were collected.…”
Section: Discussionmentioning
confidence: 99%
“…Only in 133 papers (45 %), the timing of review after non-surgical periodontal therapy was reported. This ranged between 2 weeks [28] and 6 months [11,29,30]. The clinical and radiographic baseline of the studies was usually reported to have been carried out at this stage (2 weeks to 6 months after NSPT), although sometimes it was not clear exactly when the baseline measurements were collected.…”
Section: Nspt Outcomesmentioning
confidence: 99%
“…Of note, REC values for conservative/minimally invasive procedures tend to be lower than those reported for access flap surgery/GTR (Tables 2 and 3), suggesting that minimally invasive techniques are better suited for areas requiring preservation of esthetics. Nevertheless, it is important to consider that the presence of either a non‐supportive defect anatomy (OR = 58.8) or thin‐scalloped gingival biotype (OR = 76.9) was identified as a risk factor for REC on the midfacial aspect 88 . These findings have significant implications in the esthetic zone, in which minimizing REC is paramount.…”
Section: The Relationship Of Regenerative Treatment To Endodontic Andmentioning
confidence: 99%